Communication Patterns, Ukhuwah, and the Digital Environment in Online Gaming Media: A Netnographic Study of the r/Furinamains Community - Emeraldien, Fikry; Nur Azizi Juliansyah,; Mahmud Syakiran bin Shahran, (Jurnal Komunikasi Islam, 2025)
This study examines the dynamics of communication patterns within the Reddit community r/furinamains, which centers around Furina, a character from the game Genshin Impact. The research aims to gain a deeper understanding of how Furina’s fans interact within this virtual space. A qualitative netnographic approach was employed as the research method. Data were collected through observation and documentation. The subjects of this study include posts, comments, and discussions that take place within the r/furinamains subreddit. The findings reveal that this interactive space fosters identity formation, digital solidarity, and collective emotional expression within the realm of popular media culture. The discussion considers the ethical context of communication and the values of ukhuwah (brotherhood) that support the creation of a healthy digital environment.